2016
DOI: 10.1002/ange.201603464
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing DNA Towards Low‐Energy Electrons with 2‐Fluoroadenine

Abstract: 2-Fluoroadenine ( 2F A) is atherapeutic agent, which is suggested for application in cancer radiotherapy. The molecular mechanism of DNAr adiation damage can be ascribed to as ignificant extent to the action of low-energy (< 20 eV) electrons (LEEs), which damage DNAbydissociative electron attachment. LEE induced reactions in 2F Aa re characterized both isolated in the gas phase and in the condensed phase when it is incorporated into DNA. Information about negative ion resonances and anion-mediated fragmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…DNA single-strand breaks can be induced by LEEs via DEA within several resonances below 12 eV (depending on the system under study resonances peaking around1 0, 7, 5.5, 2.2 and 1eVh ave been reported). [6][7][8][9][10][11][12] In av ery recent study the energy-dependenceo fLEE-induced strand breakage in two different oligonucleotides has been determined. [12] Ab road resonance peakinga round 7eVw as found whereas resonances at lower energies are of minor importance for the strand breakage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA single-strand breaks can be induced by LEEs via DEA within several resonances below 12 eV (depending on the system under study resonances peaking around1 0, 7, 5.5, 2.2 and 1eVh ave been reported). [6][7][8][9][10][11][12] In av ery recent study the energy-dependenceo fLEE-induced strand breakage in two different oligonucleotides has been determined. [12] Ab road resonance peakinga round 7eVw as found whereas resonances at lower energies are of minor importance for the strand breakage.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative pathway for dissociation after electron attachment is autoionization of the extra electron accompanied by excitation into a dissociative state (neutral dissociation). DNA single‐strand breaks can be induced by LEEs via DEA within several resonances below 12 eV (depending on the system under study resonances peaking around 10, 7, 5.5, 2.2 and 1 eV have been reported) . In a very recent study the energy‐dependence of LEE‐induced strand breakage in two different oligonucleotides has been determined .…”
Section: Introductionmentioning
confidence: 99%
“…[49] By using the DNA origami technique it was demonstrated that incorporation of 2F Ai nto oligonucleotides leads to an enhancemento fe lectron-induced strand breaks by af actor of 1.6-1.7 at the electron energies of 5.5, 10.0 and 15.0 eV (see Figure 5). [35] At the same time the strand break cross-sections are clearly energy-dependent with the highest cross-section found at 5.5 eV,w hich confirms that strand breakage occurs by resonant DEA. Indeed, gas-phase DEA measurements of 2F Ah ave shown ac lear DEA resonance at around 5.5 eV,w hich results in the abstractiono fHand F from 2F A[ Eq.…”
Section: Overview Of the Most Important Classes Of Radiosensitizers Amentioning
confidence: 55%
“…The strand breaks are quantified in terms of absolutec ross-sections for SSBs. [18] This technique allows to study the sequence dependenceo f low-energy radiation-induced strand breaks, [18,19] the effect of radiosensitizers, [18,34,35] and highero rder DNA structures. [34] The error in the measurements is typicallyq uite small (in the range of 1-15 %), [36] and recently,w ec ould show that ag reater structural variation of the target sequences resultsi nal arger experimentale rror.…”
Section: Experimental Challengesmentioning
confidence: 99%
“…Following selective radiation exposure, the absolute cross-section of DNA strand breakages was directly quantified by the resultant streptavidin patterns atop the DNA origami. This elegant approach was used to assess the radiation susceptibility of G-quadruplex-rich telomeric DNA regions [82], the impact on specific DNA sequences [83] and the effects of several clinically relevant radiotherapy photosensitisers [84] [85]. This concept can be expanded through the introduction of DNA aptamers to remove the limitation of detection via hybridisation or damage of nucleic acids.…”
Section: Biosensing and Assaysmentioning
confidence: 99%